A good woman - Steel, Danielle (New York : Delacorte Press, 2008)
An American society girl who made a new life as a doctor in World War I France returns to New York.
Keywords: Upper class women -- Fiction; Married women -- Fiction; Rich people -- Fiction; World War, 1914-1918 -- France -- Fiction; Americans -- France -- Fiction; Military nursing -- Fiction; New York (N. Y.) -- Fiction; Love stories